10-Alkenylphenothiazines; 1; Synthesis and cis,trans-isomerization of 10-propenylphenothiazines; Chemistry of Heterocyclic Compounds; Vol. 22, iss. 1 - Anfinogenov V. A.; Napilkova O. A.; Sirotkina E. E.; Filimonov V. D. Viktor Dmitrievich; Ogorodnikov V. D. (1986, 1986)
Title screen